Mind the body: an exploration of bodily self-awareness - Vignemont, Frédérique de (Oxford University Press, 2018)
Mind the Body' is the first comprehensive treatment of bodily awareness. Frédérique de Vignemont seeks to answer questions such as: how do I perceive my body? How do I perceive other people's bodies? Can I really feel your pain? What makes me feel this specific body is my own? Why do I care about it? To what extent can I feel an avatar's body as my own? To answer these questions, we need a better understanding of the various aspects of bodily self-awareness, including the spatiality of bodily sensations, their multimodality, their role in social cognition, their relation to action, and to self-defence. This volume combines philosophical analysis with recent experimental results from cognitive science, leading us to question some of our most basic intuitions